Aircraft system-level diagnosis with emphasis on maintenance decisions - Skliros, Christos; Ali, Fakhre; King, Steve; Jennions, Ian (SAGE, 2021)
This paper proposes a diagnostic technique that can predict component degradation for a number of complex systems. It improves and clarifies the capabilities of a previously proposed diagnostic approach, by identifying the degradation severity of the examined components, and uses a 3D Principal Component Analysis approach to provide an explanation for the observed diagnostic accuracy. The diagnostic results are then used, in a systematic way, to influence maintenance decisions. Having been developed for the Auxiliary Power Unit (APU), the flexibility and power of the diagnostic methodology is shown by applying it to a completely new system, the Environmental Control System (ECS). A major conclusion of this work is that the proposed diagnostic approach is able to correctly predict the health state of two aircraft systems, and potentially many more, even in cases where different fault combinations result in similar fault patterns. Based on the engineering simulation approach verified here, a diagnostic methodology suitable from aircraft conception to retirement is proposed.
Keywords: Aeronautical asset management; aeronautical maintenance; aerospace maintenance; condition based maintenance; failure detection; fault diagnostics; fault isolation; fault monitoring